XY sex reversal associated with a deletion 5' to the SRY "HMG box" in the testis-determining region. - McElreavy, K (1992)
The human testis-determining factor resides within a 35-kilobase (kb) region of the Y chromosome immediately adjacent to the pseudoautosomal boundary. A candidate gene for human sex determination (SRY) was isolated in this region. Here, we describe a study of 25 cases of XY females with pure gonadal dysgenesis for mutations on the Y chromosome short arm, including SRY. Southern blotting revealed a sex-reversed female harboring a deletion extending from approximately 8 kb from the pseudoautosomal boundary of the Y chromosome to at least 33 kb and no more than 60 kb upstream, toward the centromere. The deletion begins no more than 1.8 kb upstream from the first ATG of the SRY open reading frame present in the clone pY53.3. To our knowledge, no mutation has been described previously outside the SRY "HMG box" on the short arm of the Y chromosome, which is associated with sex reversal. Since the 5' extent of the SRY transcriptional unit has not been defined, the deletion may remove upstream exons of SRY and/or transcriptional regulatory motifs, either situation resulting in lack of testicular development. It cannot be formally excluded that the mutation removes a second locus, independent of SRY, that is critical for sex determination. Denaturant gradient gel electrophoresis analysis of the SRY open reading frame in the remaining 24 cases revealed de novo single base-pair transitions in the SRY conserved domain in 4 cases.